New records of Schizopteridae (Heteroptera: Dipsocoromorpha) from Southern Brazil - Morales, Irina; Cipola, Nikolas G. (Entomological Communications, 2020)
Here Schizopteridae is registered for the first time in Paraná State with the record of four species, being one to generic level, Glyptocombus sp. The three nominal species recorded are: Schizoptera (Schizoptera) apicalis Reuter, 1882, Schizoptera (Cantharocoris) reitteri Reuter, 1891, and Ptenidiophyes mirabilis Reuter, 1891, all only recorded from type locality. The Schizopteridae fauna of Brazil is now composed of 22 nominal species in 13 genera, recorded in nine Brazilian states, plus the genus Glyptocombus recorded in the South and Southeast regions of the country.